2023
DOI: 10.1007/s40820-023-01055-z
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of High-Performance PEO/Ceramic Composite Solid Electrolytes for Lithium Metal Batteries

Abstract: Composite solid electrolytes (CSEs) with poly(ethylene oxide) (PEO) have become fairly prevalent for fabricating high-performance solid-state lithium metal batteries due to their high Li+ solvating capability, flexible processability and low cost. However, unsatisfactory room-temperature ionic conductivity, weak interfacial compatibility and uncontrollable Li dendrite growth seriously hinder their progress. Enormous efforts have been devoted to combining PEO with ceramics either as fillers or major matrix with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 203 publications
0
24
0
Order By: Relevance
“…Many studies have demonstrated that the introduction of different fillers into polymer electrolytes produces different effects . The addition of fillers can suppress the enhancement of the mobility of lithium ions by generating more amorphous regions. , Additionally, fillers can modify the redox state of polymer electrolytes, increase their chemical stability, and minimize the occurrence of interfacial side reactions. Yi Cui and his team from Stanford University carried out the in situ growth of SiO 2 nanorods on PEO.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that the introduction of different fillers into polymer electrolytes produces different effects . The addition of fillers can suppress the enhancement of the mobility of lithium ions by generating more amorphous regions. , Additionally, fillers can modify the redox state of polymer electrolytes, increase their chemical stability, and minimize the occurrence of interfacial side reactions. Yi Cui and his team from Stanford University carried out the in situ growth of SiO 2 nanorods on PEO.…”
Section: Introductionmentioning
confidence: 99%
“…As early as 1998, Croce et al demonstrated that adding TiO 2 and Al 2 O 3 fillers to PEO-LiClO 4 can improve ionic conductivity to 10 –4 and 10 –5 S cm –1 at 50 and 30 °C, respectively. Encouraged by this pioneering work, researchers have undertaken continuous efforts to optimize ionic conductivity and mechanical properties by adding a diversity of ceramic fillers for PEO-based composite solid electrolytes (CSEs). , However, the lower ionic conductivity, poorer ion migration, and interfacial compatibility have led to their lack of practical application. Typically, ceramic fillers include Li + insulative fillers (such as TiO 2 , SiO 2 , and Al 2 O 3 ) and Li + conductive fillers (such as Li 7 La 3 Zr 2 O 12 and Li 0.33 La 0.557 TiO 3 ), and the enhanced ionic conductivity mainly is attributed to the increased concentration of amorphous phases in the PEO .…”
Section: Introductionmentioning
confidence: 99%
“…However, the high crystallinity of PEO at room temperature gives rise to inferior ionic conductivity (<10 –5 S cm –1 ) and Li + transference number (0.2–0.4) . Thus, the vast majority of PEO-based solid polymer electrolytes were operated at higher temperatures for long-term cycling, causing additional energy consumption and cost for heating up and restricting low-temperature applications. , Meanwhile, the poor mechanical strength and vulnerability against oxidation (>4.0 V) further hinder their practical implementation, especially for high-voltage lithium metal batteries . In recent years, enormous efforts have been committed to developing a variety of strategies such as introducing inorganic ceramic fillers, grafting copolymers, and cross-linking with PEO to facilitate the formation of local amorphous regions. , Among them, introducing ceramic fillers to PEO is regarded as one of the effective approaches to comprehensively enhance ionic conductivity, mechanical tolerance, and electrochemical stability …”
Section: Introductionmentioning
confidence: 99%
“…18,21 Up to now, due to its excellent film-forming performance and electrochemical stability, poly(ethylene oxide) (PEO) has been widely studied and applied in all solid-state Li + batteries. 22,23 However, the low ionic conductivity and narrow electrochemical stability window of PEO-based SPEs at room temperature severely restrict their practical application in lithium-ion batteries. Past research has shown that the fundamental reason for Li + transport is the segmental motion of PEO molecular chains in the amorphous part, and the method of adding fillers to increase the amorphous phase and improve its mechanical and electrochemical performance becomes increasingly popular in recent years.…”
Section: ■ Introductionmentioning
confidence: 99%
“…At present, lithium–sulfur (Li–S) batteries have been considered as an advanced battery system with broad application prospects due to their ultrahigh theoretical energy density and low cost. However, compared to traditional Li + battery systems, the commercialization of Li–S batteries still faces challenges. , First, the “shuttle effect” caused by the migration of lithium polysulfide (LiPS) intermediates within the battery reduces the cycling ability. In addition, the generation of lithium dendrites, highly flammable organic electrolytes, and thermal runaway caused by exothermic redox reactions have become key factors limiting the development of Li–S batteries. In order to further promote the commercialization of Li–S batteries, important strategies are mainly focused on sulfur cathode composites; however, safety concerns remain. At present, replacing traditional liquid electrolytes with solid electrolytes is generally considered to be a more effective measure to overcome the obstacles to the development of Li–S batteries. , Compared with inorganic-based solid electrolytes, , solid polymer electrolytes (SPEs) have the advantages of good flexibility and easy film formation, which can make the electrode interface in close contact. , Up to now, due to its excellent film-forming performance and electrochemical stability, poly­(ethylene oxide) (PEO) has been widely studied and applied in all solid-state Li + batteries. , However, the low ionic conductivity and narrow electrochemical stability window of PEO-based SPEs at room temperature severely restrict their practical application in lithium-ion batteries. Past research has shown that the fundamental reason for Li + transport is the segmental motion of PEO molecular chains in the amorphous part, and the method of adding fillers to increase the amorphous phase and improve its mechanical and electrochemical performance becomes increasingly popular in recent years .…”
Section: Introductionmentioning
confidence: 99%